Generation of Natural Killer Cell Memory during Viral Infection - O'Sullivan, Timothy E. (J Innate Immun, 2015)
Immunological memory is classically regarded as an attribute of antigen-specific T and B lymphocytes of the adaptive immune system. Cells of the innate immune system, including natural killer (NK) cells, have been considered short-lived cytolytic cells that can rapidly respond against pathogens in an antigen-independent manner and then die off. However, NK cells have recently been described to possess traits of adaptive immunity, such as clonal expansion after viral antigen exposure to generate long-lived memory cells. In this review, we will discuss the current evidence for viral-induced NK cell memory in both mice and humans.